The coherence of basketballs, players in (15-16) age of high school tournaments Educational Karkh/ 3 - Khuair, Naseer (Journal of Physical Education, 2015)
The research (5) Parts: (Part 1) It contained the introduction and its importance, Which Summarizes in the Cohesion of the sport’s team , it is the most important factor of the Successful team. The problem Crystallizes if there was a Lack of Cohesions of the sport’s team and if the relations characterize to compete. The study’s question is:- (What is the extent of the cohesion of basketballs, players in the secondary school tournaments Karkh /3)? (Part 2) It includes a theoretical and similar studies. (Part 3)) It includes Contained research’s methodology and Procedures the researcher and descriptive method. The study contacted on a Sample (80) basketballs, players for the Same school. The study were distributed a questionnaire the cohesion of the sport’s team and been used statistical the (spss) in the analysis of results. (Part 4) A section views the results , analysis and discussions. The results showed that the degree of the cohesion of sample’s players a large degree. The percentage of response to (75.6 %). (Part 5) It includes Conclusions and recommendation which were represented in important of focusing on manifestations and aspects the positive which is characterized by the Panel, and concern for the development the spirit of Victory with the players, and that the acquires each player in the team the conviction of the importance of his role and extends this concept for the player the reserve or some players who do not taking a direct in some the competitive matches